Rare histotypes of canine mammary neoplasms - Salgado, Breno S. [UNESP]; Monteiro, Lidiane Narducci; Cassali, Geovanni Dantas; Rocha, Noeme Sousa [UNESP]; Gärtner, Maria de Fatima rodrigues (My University, 2014)
Mammary neoplasms in dogs are heterogeneous in its presentation, classification, and clinical course. In the last years, histotypes that differ from those described in the World Health Organization classification of mammary gland tumors in dogs and cats were reported and raised a question about the importance of correctly diagnosing them. This article brings information on 4 subtypes with a very concise histopathology description and parameters helpful in the clinic. Accordingly, the aim of this paper is to provide data for mammary neoplasms caregivers which will enable a better understanding of the disease in those animals
Keywords: Mammary carcinoma; Diagnosis; Histopathology; Dog